Burning Mouth Syndrome Treated with Mandibular and Maxillary Nerve Blocks - Jamal Hasoon; Christopher Robinson; Ivan Urits; Omar Viswanath; Alan D. Kaye (Health Psychology Research)
Burning mouth syndrome is a condition characterized by a painful burning sensation in the oral mucosa lasting at least 3-6 months with no definitive etiology. The pathophysiology is not well understood, though there appears to be a connection with other neuropsychiatric conditions such as depression, anxiety, and mood disorders. We briefly discuss our experience with a patient who suffered from this conidtion and how it was treated with mandibular and maxillary nerve blocks after failing more conservative pharmacological options.